From Parents' Cradle to Children's Career: Intergenerational Effects of Parental Investments - Sander de Vries; Nadine Ketel; Maarten Lindeboom (Institute of Labor Economics (IZA), 2024)
There is a clear consensus that childhood experiences shape adult success, yet there is limited understanding of their impact on future generations. We proxy parental investments during childhood with birth order and study whether disadvantages due to lower investments are transmitted to future generations. Birth order effects on the first generation are large, apply to 80% of the population, and can be identified with relatively mild assumptions. Using cousin comparisons in Dutch administrative data, we find that around 20 percent of the income disadvantages are transmitted. Additionally, we find sizeable decreases in children's education and increases in boys' criminal behavior.
Keywords: D19; I24; J13; 330; intergenerational mobility; birth order; extended family; education; crime